Silicon-catalyzed depolymerization of polyethers: pushing scope, practicability and mechanistic understanding - Ansmann, Nils; Johann, Kerstin; Favresse, Philippe; Johann, Tobias; Fiedel, Michael; Greb, Lutz (ChemCatChem, 2024)
The depolymerization of polyethers is a sustainable yet challenging opportunity for a circular economy in materials processing. While we recently identified silicon Lewis superacids as promising catalysts for this transformation, limited scope (e. g., terminal OH groups not tolerated) and strict requirements for anhydrous conditions hampered wider applicability. In the present work, the impact of different polyether structures and reaction conditions were evaluated. By doing so, the generality for structural variations was confirmed and substantial improvements made the depolymerization feasible for large-scale applications under ambient conditions. Based on systematic experimental screenings, a refined mechanistic model of the depolymerization process is developed.